METHODICAL APPROACH TO ASSESSMENT OF THE MORPHOLOGICAL CHANGES IN ACUPUNCTURE OF TONGUE - N. Pirovski; N. Dimitrov; D. Atanasova (Trakia Journal of Sciences)
Changes occurring in acupuncture and sublingually administration of medicines also have a morphological basis, which can be objectively assessed. Objective: Refine of the methodology for evaluating morphological changes associated with tongue acupuncture. Material and methods: Selection of experimental animals and appropriate protocol for material collection, fixation, staining and counting of selected morphological structures and elements. Results: The samples fixed with formalin 10% were fixed well, the consistency of the tissues remained hard and the cuts were obtained well in all thicknesses (from 5 to 15 μm). Cuts from 5 to 7 μm are suitable for visualizing the structure of the tongue. The sagittal cuts provide the largest area for single-cut exploration, as well as are more suitable than others to track the acupuncture channel in the chosen for our study point. Conclusions: The study can be carried out in rats, but if possible, it is preferable to take the material from pigs. The use of formalin 10% gives a better texture to the material and facilitates the cutting with the microtome. It is necessary to use a variety of colorings due to the wide range of structures that are involved with the acupuncture needle tract.